2014
DOI: 10.1038/ijo.2014.142
|View full text |Cite
|
Sign up to set email alerts
|

Usual energy and macronutrient intakes in 2–9-year-old European children

Abstract: on behalf of the IDEFICS and the I.Family consortia OBJECTIVE: Valid estimates of population intakes are essential for monitoring trends as well as for nutritional interventions, but such data are rare in young children. In particular, the problem of misreporting in dietary data is usually not accounted for. Therefore, this study aims to provide accurate estimates of intake distributions in European children. DESIGN: Cross-sectional setting-based multi-centre study. SUBJECTS: A total of 9560 children aged 2-9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 56 publications
(65 reference statements)
2
33
2
Order By: Relevance
“…Energy intakes are often overestimated with FFQs compared to 24HR (which was found in this study, manuscript in preparation). Since under and over reporting in food intake studies are well known, participants who reported consuming less than 0.79 or above 2.4 times their basal metabolic rate calculated using Schofield formula were therefore excluded from diet‐related analysis . Eighty‐five participants in 2013 and 84 in 2014 were included to generate the aggregated FFQ food intake results .…”
Section: Methodsmentioning
confidence: 99%
“…Energy intakes are often overestimated with FFQs compared to 24HR (which was found in this study, manuscript in preparation). Since under and over reporting in food intake studies are well known, participants who reported consuming less than 0.79 or above 2.4 times their basal metabolic rate calculated using Schofield formula were therefore excluded from diet‐related analysis . Eighty‐five participants in 2013 and 84 in 2014 were included to generate the aggregated FFQ food intake results .…”
Section: Methodsmentioning
confidence: 99%
“…Questionnaires were used to collect parental information such as the educational level of both parents. The dietary intake of the previous 24 hours was assessed with a computer-assisted 24 hour dietary recall as described in detail elsewhere (39,40).…”
Section: Medical History and Lifestyle Factorsmentioning
confidence: 99%
“…Many foods were country-specific. In IDEFICS, SACINA was used to estimate energy and nutrient intakes 18,19 and also factors associated with parental misreporting of their children's dietary intake. 20 The main factors influencing misreporting were low socioeconomic status, high child body mass index (BMI), high parental BMI, mother vs father as proxy reporter, and high parental concern about child's weight status.…”
Section: Materials and Methods Participantsmentioning
confidence: 99%